2012
DOI: 10.1016/j.cub.2012.07.069
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Computational Model of the Dynamic 3D Interphase Yeast Nucleus

Abstract: Our results suggest that large-scale yeast nuclear architecture can be largely understood as a consequence of generic properties of crowded polymers rather than of specific DNA-binding factors and that configurations of chromosomes and DNA contacts are dictated mainly by genomic location and chromosome lengths. Our model provides a quantitative framework to understand and predict large-scale spatial genome organization and its interplay with functional processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
207
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(225 citation statements)
references
References 49 publications
17
207
0
Order By: Relevance
“…This description was recently complemented by the first Hi-C comprehensive maps (Rodley et al 2009;Duan et al 2010), which confirmed an organization guided by nuclear landmarks, including TEL that congregate in foci (Gotta et al 1996;Schober et al 2008). Recent Brownian dynamics (BD) simulations confirmed this structural model by recapitulating Hi-C and imaging data, assuming that physical tethering at TEL and CEN and volume exclusion were driving chromosome conformations (Tjong et al 2012;Wong et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 65%
“…This description was recently complemented by the first Hi-C comprehensive maps (Rodley et al 2009;Duan et al 2010), which confirmed an organization guided by nuclear landmarks, including TEL that congregate in foci (Gotta et al 1996;Schober et al 2008). Recent Brownian dynamics (BD) simulations confirmed this structural model by recapitulating Hi-C and imaging data, assuming that physical tethering at TEL and CEN and volume exclusion were driving chromosome conformations (Tjong et al 2012;Wong et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 65%
“…These observations indicate that centromere clustering can shape the interphase genome architecture by imposing strong geometrical constraints on chromosome positioning. Notably, in other organisms, such as yeasts (6,44,(49)(50)(51)(52) and Drosophila melanogaster (8,9), centromere clustering plays a prominent role in shaping the interphase genome structures. A model based on interchromosomal interactions formed by only subcentromeric regions suffices to reproduce the correct radial positions of all chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…c . This explains the intrachromosomal contact frequency P (s) ∼ s −1.5 for yeast genome, pointing to an equilibrium globule [8,[37][38][39].…”
mentioning
confidence: 99%
“…Dynamical implication of our finding φ bac φ yeast < φ ∞ c φ human < φ virus , and the correlations of φ yeast < φ ∞ c with P (s) ∼ s −1.5 for budding yeast [37] and φ ∞ c φ human with P (s) ∼ s −1 for mature human cells [9] provide a new framework for understanding the origin of qualitatively distinct chromosome organization in various organisms and cell types. Given that cellular environment is replete with crowding particles, the volume fractions estimated here for different organisms may well be only lower bounds, and thus we expect that glassy dynamics is prevalent especially in higher-order organisms.…”
mentioning
confidence: 99%